How do experts reporting for the legal process validate symptoms? The results of a survey. (April 2014) - Allcott, Drew; Anderson, Stuart; Friedland, Daniel; Leng, Nicholas; Gross, Michael; Skelton-Robinson, Martin; Weller, Malcolm
This article examines the views of experts from a range of disciplines and how they view symptoms given to them by claimants in matters of personal injury or medical negligence assessments. The survey was carried out in 2009 and looks at current practice and attitudes from a number of different disciplines. The survey included questions looking at what percentage of cases were thought to be genuine, symptoms most likely to be elaborated, methods for assessing symptom validity, and documentary evidence required for a report. This article highlights the importance of looking at symptom validation in the legal process.